The Impact of Physical Activity on Digestive System Diseases - Zabawa, Bartłomiej; Sadowski, Jakub; Mól, Piotr; Papież, Łukasz Stanisław; Dołęga, Julia; Krzykawski, Karol; Maciejczyk, Tomasz; Sieńko, Antoni; Łabuś, Małgorzata; Hudzińska, Patrycja (Quality in Sport, 2024)
Introduction: Digestive system diseases, including IBD, and GERD, are prevalent health concerns worldwide. Physical activity, widely acknowledged for its health benefits, has emerged as a promising area of research for its potential in mitigating symptoms and influencing risk factors associated with digestive system diseases. This study aims to critically assess existing evidence on the role of physical activity in the prevention, symptom management, and progression of prevalent digestive disorders. Materials and Methods: A systematic review of pertinent studies was conducted through comprehensive searches in databases including PubMed, NCBI and Google Scholar. The data were sourced from clinical and experimental studies, evaluated for methodological rigor, participant characteristics, and therapeutic outcomes. State of knowledge: The analysis demonstrated that physical activity can exert beneficial effects on digestive health through mechanisms such as enhanced gut motility, reduced inflammation, and increased microbiota diversity. Moderate-intensity aerobic exercise was associated with reduced risk and symptom improvement in patients with IBS and IBD, while high-intensity exercise showed variable effects, with potential symptom exacerbation in certain cases. Additionally, exercise correlated with a lower incidence of GERD, likely due to benefits in weight management. Despite these positive associations, inconsistencies in study design and exercise protocols underscore the need for standardized guidelines on physical activity tailored to specific digestive conditions. Conclusions: Physical activity appears to play a beneficial role in managing and potentially preventing certain digestive system diseases. While moderate exercise shows promise in symptom alleviation and risk reduction, further research is necessary to establish clear, condition-specific exercise recommendations.